Combined mitral valve replacement associated with the Bentall procedure, diaphragmatic hernia repair and reconstruction of the pectus excavatum in a 26-year-old patient with Marfan syndrome - Stępiński, Piotr; Stankowski, Tomasz; Aboul-Hassan, Sleiman Sebastian; Szymańska, Anna; Marczak, Jakub; Cichoń, Romuald (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
A 26-year-old man with Marfan syndrome was admitted as an emergency patient with ascending aorta aneurysm, severe mitral and aortic regurgitation, diaphragmatic hernia and pectus excavatum. After completion of diagnostics a combined surgical procedure was performed.